SATU DEKADE DESA BOTUNGOBUNGO - Renol Hasan; Sri Milawati Pandju; Mohamad Wantu (Jambura History and Culture Journal, 2020)
This study aims to reveal the One Decade of botungobungo village, using qualitative historical research methods. Qualitative research is a type of research whose findings are not obtained through statistical procedures or other forms of calculation and seeks to understand and interpret the meaning of an event of human behavior interaction in certain situations according to the researcher's own perspective. The collection of sources in this study was carried out with the initial stage of observing the research location and then conducting interviews with the local community to obtain relevant data related to the research title and continued with writing the research results juxtaposed with existing concepts. So that this research can reveal related research topics.